Prognostic Significance of Oxidative Stress Biomarkers and Novel Hematological Inflammatory Indices in Colorectal Cancer: A Prospective Observational Study - Răzvan Alexandru Marinescu; Daniela Marinescu; Ana-Maria Ciurea; Lidia Boldeanu; Marius Bică; Ștefan Pătrașcu; Victor Dan Eugen Strâmbu; Petru Adrian Radu; Petrica Popa; Mihail Virgil Boldeanu; Styliani Laskou; Valeriu Șurlin (Medicina, 2026)
Background and Objectives: Oxidative stress and chronic inflammation are closely interconnected processes involved in colorectal cancer (CRC) development and progression. However, the relationships between oxidative stress biomarkers, emerging hematological inflammatory indices, clinicopathological characteristics, and survival outcomes remain insufficiently characterized. This study evaluated circulating levels of 8-epi-prostaglandin F2α (8-epi-PGF2α), malondialdehyde (MDA), and superoxide dismutase 1 (SOD1), together with conventional and novel inflammatory indices, including the mean corpuscular volume-to-lymphocyte ratio (MCVL) and cumulative inflammatory index (IIC), in patients with CRC. Materials and Methods: This prospective observational study included 140 patients with histologically confirmed CRC and 40 healthy controls. Serum concentrations of 8-epi-PGF2α, MDA, and SOD1 were measured by ELISA, and hematological inflammatory indices were calculated from complete blood counts. Associations with clinicopathological characteristics were evaluated using non-parametric analyses with correction for multiple testing where appropriate. Spearman correlations with false discovery rate correction were used to assess oxidative–inflammatory associations. Prognostic analyses included 24-month time-dependent receiver operating characteristic (ROC) analysis accounting for censoring, Kaplan–Meier analysis, and Cox proportional hazards regression for overall survival (OS) and progression-free survival (PFS). Results: CRC patients exhibited significantly higher serum levels of 8-epi-PGF2α (p = 0.016), MDA (p < 0.001), and SOD1 (p < 0.001) than controls. Oxidative stress biomarkers differed significantly across TNM stage, nodal status, and histological grade, although the observed patterns were not uniformly progressive with disease stage. After false discovery rate correction, MDA retained significant correlations with multiple hematological inflammatory parameters, whereas SOD1 showed a more restricted correlation profile and 8-epi-PGF2α showed no significant correlations. At 24 months, MDA demonstrated the highest time-dependent discrimination for OS (AUC = 0.920; bootstrap 95% CI: 0.834–0.978), whereas its discrimination for PFS was modest (AUC = 0.636; bootstrap 95% CI: 0.487–0.773). High MDA, defined by the internally derived 24-month threshold, was associated with shorter PFS after adjustment for age, sex, and TNM stage (HR = 2.49, 95% CI: 1.29–4.80; p = 0.006) and, separately, metastatic status (HR = 2.40, 95% CI: 1.22–4.72; p = 0.011). However, when modeled continuously, MDA was no longer significantly associated with PFS after multivariable adjustment. Conclusions: CRC was associated with increased circulating oxidative stress biomarkers, with MDA showing the most consistent relationships with systemic inflammatory parameters and survival outcomes. Its prognostic association with PFS was dependent on the modeling approach, while its high discrimination for 24-month OS should be interpreted cautiously because of the limited number and metastatic restriction of death events. These findings identify MDA as a promising candidate oxidative–inflammatory marker warranting external validation rather than an independently established prognostic biomarker.